Getting ready for the millennium round trade negotiations - Díaz-Bonilla, Eugenio; Robinson, Sherman (International Food Policy Research Institute, 1999)
When trade ministers meet in the United States( ) late this year, they may launch a new round of global trade talks under the auspices of the World Trade Organization (WTO). If the ministers indeed initiate this “millennium round,” agriculture will be part of it. Otherwise, agricultural negotiations will proceed on their own, since Article 20 of the Uruguay Round (UR) Agreement on Agriculture states that agricultural negotiations should be resumed during 1999.